2019
DOI: 10.1038/s41598-019-45897-3
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally-Controlled Near Infrared Spectroscopic Imaging of Bone Water

Abstract: We have designed an environmentally-controlled chamber for near infrared spectroscopic imaging (NIRSI) to monitor changes in cortical bone water content, an emerging biomarker related to bone quality assessment. The chamber is required to ensure repeatable spectroscopic measurements of tissues without the influence of atmospheric moisture. A calibration curve to predict gravimetric water content from human cadaveric cortical bone was created using NIRSI data obtained at six different lyophilization time points… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…It is likely that future studies can address this in a more quantitative manner. Recent studies that assessed collagen with NIR radiation found that collagen peaks are present at ~6800 cm ‑1 and ~4600 cm −1 . In this study, we did find a positive correlation between the peak intensity at 6800 cm −1 and cortical area, and a strong negative correlation between that peak and age, illuminating the importance of collagen in the cortical part of the bone and its decrease as we age.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…It is likely that future studies can address this in a more quantitative manner. Recent studies that assessed collagen with NIR radiation found that collagen peaks are present at ~6800 cm ‑1 and ~4600 cm −1 . In this study, we did find a positive correlation between the peak intensity at 6800 cm −1 and cortical area, and a strong negative correlation between that peak and age, illuminating the importance of collagen in the cortical part of the bone and its decrease as we age.…”
Section: Discussionmentioning
confidence: 91%
“…This could indicate that the detected NIR water peaks arise from bound, as opposed to free, water, which are primarily associated with mineral or collagen . Interestingly, the water peak at 8680 cm −1 did have a strong positive correlation with DXA z ‐score, indicating that water is a major contributor to bone health as other studies have shown . In contrast, the 5300 cm −1 water peak did not correlate with DXA z ‐score, which could be due to lack of sufficient sensitivity of the NIR frequency via transcutaneous assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the high cost and complexity, MRI examinations are impossible to replace standard DEXA (Dual-Energy X-ray Absorptiometry) measurements with more advanced MRI analysis. In prior studies, optical spectroscopic techniques have been used to evaluate how the alterations of bone composition contribute to bone quality changes related to aging, disease, or injury [12][13][14][15][16][17][18]. However, traditional optical techniques suffer from limited spatial resolution and the overwhelming optical scattering in biological tissues, thus reducing the efficacy of skeletal imaging in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Typical absorbance bands of relevance to the analysis of NIR spectra of connective tissues [41][42][43][44][45][46][47][48][49]…”
mentioning
confidence: 99%